O44. The differences in induction and repair of DNA DSB induced by 30 kV X-rays, fast neutrons and γ-rays. (September 2016) - Depuydt, J.; Beukes, P.; Baert, A.; Vandersickel, V.; Thierens, H.; Slabbert, J.P.; Vral, A.
Abstract : Introduction: Radiation is known to be an inducer of cancer, however, radiation is also often used in a useful manner in radiotherapy and diagnostic imaging. In this research, we investigated the efficiency of different radiation qualities to induce DNA damage and how this damage is repaired by different cell types. Material and methods: Lymphocytes, MCF-10A cells and epithelial cells in resected breast tissue were irradiated with high LET fast neutrons and low LET 30 kV X-rays and 1.2 MeV 60 Co γ -rays. By means of the γ H2AX-foci assay we analyzed the efficiency in DNA DSB-induction by the different radiation qualities. With the micronucleus (MN) assay we analyzed how efficient these DSB, induced by different radiation qualities, were repaired by the cell. Results: While a lower number of radiation-induced γ H2AX-foci was observed for neutron radiation compared to γ -rays until about 4h post-IR, foci repair was slower and more residual foci were present at later time points. Furthermore, neutrons seem to be more effective in inducing MN. Irradiation of human lymphocytes with 30kV X-rays resulted in a modest increase in the number of γ H2AX-foci compared to γ -rays, but these DSB were more difficult to repair correctly by the cell and resulted in a more pronounced increase in MN compared to γ -rays. Furthermore, in the 0–20 mGy dose-range a low-dose hypersensitive response for DSB induction was observed in mammary epithelial cells present in resected breast tissue, probably caused by the bystander effect. Conclusion: These results are important to assess the effects of radiotherapy and may have important implications for the risk assessment of mammography screening.